The influence of irrigated agriculture, urbanisation and water scarcity on human-water system dynamics - Frawley, Imogen; Mazzoleni, Maurizio; Di Baldassarre, Giuliano; Colloff, Matthew J. (Frontiers in Water, 2025)
Large dams have become a dominant water management strategy over the last century, but they are typically managed with limited understanding of how human responses to their construction and operation influence the achievement of water management objectives. In recent years, several behavioural response patterns to large dams in human-water systems have been identified, and quantitative models developed to capture these emergent phenomena. However, there is a gap between the understanding of these phenomena in a generalised sense and communicating their relevance to water managers in local contexts. In this study we applied a generalised human-water systems model of reservoir operations during droughts and floods to two case studies in Australia; one in the water-scarce, largely agricultural Lachlan River catchment, and the other in the coastal, highly-urbanised Hawkesbury–Nepean catchment. Modelling results coupled with a qualitative review of historical socioeconomic, hydroclimatic, and water management characteristics of each case study were compared to identify potential emergent phenomena and the characteristics contributing to their development. We found reservoir effects (where increases in water storage capacity increase vulnerability to water scarcity) and lock-in behaviours are inherent risks for large reservoirs. The levee effect, whereby infrastructure reducing the probability of flooding paradoxically increases vulnerability to floods, is a risk, particularly where urbanisation is high. Sequence effects, where measures to deal with one hydrological extreme exacerbate the effects of the other extreme, are likely when operational rules constrain the adaptation of operations to hydroclimatic conditions, or when water management interactions during drought and flood are poorly understood. Where there is economic incentive to increase water usage, supply–demand cycles and rebound effects are a risk. Sensitive downstream ecosystems and high competition for limited resources make shifts in values that redirect water management priorities (pendulum swings) more likely. Identifying these emergent phenomena and their driving characteristics can help water managers identify and focus on context-specific risks to enable a proactive management approach to current and future challenges.